BAMBOO FUNGUS (PHALLUS INDUSIATUS) CULTIVATION USING VARIOUS FRUIT TREE LEAVES BENEATH SPONGE GOURD AND BITTER GOURD HOLDS - Bunroj, Ajchara (PSRU Journal of Science and Technology, 2019)
The objective of this project was to culture the bamboo mushroom on selected fruit tree leaves beneath sponge gourd and bitter gourd holds and to study the relationships between 2 factors, first factor were 2 species of climbing vegetables: bitter guard and sponge gourd, second factor were 3 types of fruit tree leaves: durian longan and lambutan. The experiments were conducted at the faculty of agricultural technology, Rambhai Barni Rajabhat University, Chanthaburi Province. The results revealed that the bamboo mushrooms cultivation beneath the bitter guard hold on durian leaves had the shortest time (38.7 days) for fruiting initiation after inoculated the bamboo mushroom spawn on mushroom growing beds but it was not significantly different at p > 0.05 from the bamboo mushroom cultivation beneath the sponge gourd hold on durian leaves and beneath sponge gourd hold on lambutan leaves which had fruiting initiation 42 and 44.7 days respectively. Bamboo mushroom cultivations beneath the bitter gourd and sponge gourd holds on durian leaves could harvest fruiting bodies 12 times and 9 times respectively during 82 days of harvesting period. Bamboo mushroom cultivation beneath the bitter gourd hold on durian leaves provided the highest number of fruiting bodies (14 fruiting bodies) and yield (348.3 grams per square meter) but not significantly different at p > 0.05 from the other treatments. Bamboo mushroom cultivation beneath sponge gourd hold on lambutan leaves produced the highest fruiting - body fresh weight (48.2 grams), fruiting - body dry weight (2.8 grams) and veil length (23.3 cm) respectively.